The role of zebrafish (Danio rerio) in dissecting the genetics and neural circuits of executive function - Parker, Matthew O.; Brock, Alistair J.; Walton, Robert T.; Brennan, Caroline H. (Frontiers in Neural Circuits, 2013)
Zebrafish have great potential to contribute to our understanding of behavioural genetics and thus to contribute to our understanding of the aetiology of psychiatric disease. However, progress is dependent upon the rate at which behavioural assays addressing complex behavioural phenotypes are designed, reported and validated. Here we critically review existing behavioural assays with particular focus on the use of adult zebrafish to explore executive processes and phenotypes associated with human psychiatric disease. We outline the case for using zebrafish as models to study impulse control and attention, discussing the validity of applying extant rodent assays to zebrafish and evidence for the conservation of relevant neural circuits.